Individual Wrong or Systemic Failure? Moral Judgements About the Integrity of Politicians in the Wake of Dutch Integrity Scandals - Willianne Van Ginkel-Kempenaar; Toon Kerkhoff (Administrative Sciences)
This article focuses on moral judgements about the integrity of politicians expressed by various actors in public opinion in the wake of Dutch integrity scandals. The research assesses the link between a supposed act on the one hand and moral judgements of the actors involved on the other in an effort to improve our understanding of how political integrity is perceived and how it is used in public and political debate. This exploratory study takes three Dutch case studies of supposed conflicts of interest. Each case offers a view on judgements concerning political integrity from various media outlets, focused on three different levels: judgements of personal integrity, role integrity and political system integrity. This novel theoretical construct serves to see whether and, if so, how moral judgements about political integrity are linked to systemic (dis)satisfaction with government and politics. In addition—and focusing on the Dutch context only—the article assesses how people’s supposed place on a political ideological spectrum from left to right might influence their moral judgement. The article underscores the theoretical notion that the meaning of political integrity is inherently subject to varied interpretation and context of place and time. This also has important practical implications for managing and improving political integrity.